Pełzaki z rodzaju Acanthamoeba jako czynnik etiologiczny zapalenia rogówki oka - Kosik-Bogacka, Danuta; Czepita, Damian; Łanocha, Natalia (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: The aim of the paper was to describe the role of amoebas of the genus Acanthamoeba in the pathogenesis of keratitis. Material and methods: A review of literature concerning the role of amoebas of the genus Acanthamoeba in the pathogenesis of keratitis was done. Results: Amoebas of the genus Acanthamoeba can be widely found in soil, air, fresh as well as saline water and as facultative parasites in humans. Amoebas of this genus are responsible for the creation of Acanthamoeba keratitis. In this paper the latest data concerning the epidemiology, diagnostic and treatment of Acanthamoeba keratitis have been cited and disscused. Conclusions: 1. Keratitis induced by amoebas of the genus Acanthamoeba are characterized as acute and difficult to treat. 2. Acanthamoeba keratitis occurs in recent years more often due to the fact that more people wear contact lenses.